2001
DOI: 10.1046/j.1439-0450.2001.00469.x
|View full text |Cite
|
Sign up to set email alerts
|

Sows Intramammarily Inoculated with Escherichia coli: Influence of Time of Infection, Hormone Concentrations and Leucocyte Numbers on Development of Disease

Abstract: The aim of this study was to identify factors that influence the development of disease in sows inoculated with Escherichia coli in the mammary gland. Ten cross-bred primiparous sows were intramammarily inoculated with living E. coli bacteria at different time points before parturition: seven sows within 48 h before parturition and three sows approximately 96 h before parturition. Before and after inoculation, blood samples and mammary gland biopsy specimens were collected and clinical observations were made. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Moreover, no differences in LPS concentrations were detected between sows with and without PDS, indicating that increased inflammation was not induced by translocation of LPS from the udder to the bloodstream ( Farmer et al, 2015 ). These results are in line with previous studies indicating that predisposing factors other than bacterial infections must be present for PDS to develop ( Magnusson et al, 2001 ; Osterlundh et al, 2002 ; Gerjets et al, 2011 ; Kaiser et al 2018b ). However, Pejsak and Tarasiuk (1989) demonstrated a greater prevalence of LPS in sows with signs of coliform mastitis compared with healthy sows, indicating that LPS could be the cause of coliform mastitis in some cases.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, no differences in LPS concentrations were detected between sows with and without PDS, indicating that increased inflammation was not induced by translocation of LPS from the udder to the bloodstream ( Farmer et al, 2015 ). These results are in line with previous studies indicating that predisposing factors other than bacterial infections must be present for PDS to develop ( Magnusson et al, 2001 ; Osterlundh et al, 2002 ; Gerjets et al, 2011 ; Kaiser et al 2018b ). However, Pejsak and Tarasiuk (1989) demonstrated a greater prevalence of LPS in sows with signs of coliform mastitis compared with healthy sows, indicating that LPS could be the cause of coliform mastitis in some cases.…”
Section: Discussionsupporting
confidence: 93%
“…The development of clinical symptoms of CM in the sow was suggested to be associated with a locally increased production of pro-inflammatory cytokines such as interleukin 1-beta (IL1-beta), IL6, IL8, and tumor necrosis factor-alpha (TNF-alpha) in response to intramammary E. coli infection [ 10 , 11 ]. Additionally, the time of infection of the mammary gland relative to parturition and the number of circulating neutrophils at the time of infection were shown to influence the development of clinical CM in the sow [ 12 ]. No published study was found regarding the inflammatory response of periparturient sows after inoculation of mammary gland with S. aureus .…”
Section: Introductionmentioning
confidence: 99%
“…Among the 117 vets that responded about their management of PBIE and chronic endometritis, it was found that none of the vets that managed a large number of mares used antibiotics for treating PBIE, whereas 38% of the vets managing a small number of mares did. For treatment of chronic endometritis, 78% applied systemic E. coli-mastitis in the sow at parturition is by several studies indicated to be a key component in the agalactia or dysgalactia postpartum, sometimes including metritis, syndrome (Kemper, 2020;Kemper et al, 2013;Magnusson et al, 2001;Persson et al, 1996), even if other factors likely contribute to this syndrome. Similar to E. coli mastitis in the cow, non-antibiotic treatments including oxytocin, which also may help curing metritis (Björkman et al, 2018), and NSAIDs are often recommended except for severe cases with high fever when antibiotics against gram-negative bacteria is justified (Farmer et al, 2019).…”
Section: Op Ti On S For Refining and Reducing Antib I Oti C Us E For ...mentioning
confidence: 99%
“…E. coli —mastitis in the sow at parturition is by several studies indicated to be a key component in the agalactia or dysgalactia postpartum, sometimes including metritis, syndrome (Kemper, 2020 ; Kemper et al, 2013 ; Magnusson et al, 2001 ; Persson et al, 1996 ), even if other factors likely contribute to this syndrome. Similar to E. coli mastitis in the cow, non‐antibiotic treatments including oxytocin, which also may help curing metritis (Björkman et al, 2018 ), and NSAIDs are often recommended except for severe cases with high fever when antibiotics against gram‐negative bacteria is justified (Farmer et al, 2019 ).…”
Section: Options For Refining and Reducing Antibiotic Use For Reprodu...mentioning
confidence: 99%